Analisis Parameter Gempabumi Dengan Struktur Geologi Di Daerah Asparaga, Gorontalo - Ratna Sari Madusila; Intan Noviantari Manyoe; Cindi Claudia Male (Universitas Negeri Gorontalo, 2021)
Gorontalo is an area located in the North Arm of Sulawesi which has a complex geological structure as a result of the submergence of the Sulawesi Sea and East Sangihe so that this area is considered an earthquake-prone area. The existence of the regional structure and the mapping of the earthquake point distribution is interesting to be studied more deeply because it affects seismic activity in the area. The purpose of this study is to analyze earthquakes in the Asparaga area based on their depth and magnitude and to relate them to the geological structures found in the study area. The earthquake data used were obtained from USGS. Satellite image data used is the SRTM satellite image. Earthquake data is mapped to produce depth maps, magnitude maps, and earthquake zoning maps. Lineament data were processed using a rosette diagram. Lineament can reflect the morphology observed on the earth's surface as a result of the activity of geological forces. The results showed that the Asparaga area had shallow earthquake depths and moderate to large magnitudes. The focus of the earthquake was right on the path traversed by the geological structure and its relatively northwest-southeast direction. The geological structure in the research location is the epicenter of the earthquake because it is crossed by regional geological structures.